Phraseology in Two Omani Undergraduate Civil Engineering Genres: The N of (the) N Pattern - Mathew, Priya (Indonesian Journal of Applied Linguistics, 2021)
The study of phraseology with respect to continuous and discontinuous frames in academic writing has gathered increasing research attention over the past decade. Their prevalence in expert writing and the influence of discipline and genre on their frequency and type have led to studies that attempted to identify the most productive discontinuous frames. The aim of this study is to investigate the pattern the N of (the) N, a prolific pattern in expert academic writing, in two Omani corpora of undergraduate Civil Engineering genres, Case Studies (CS) and Methodology Recounts (MR). The two strands of inquiry involve 1) a comparison between the semantic noun categories of the first (N1) and second noun (N2) used in this pattern and; 2) the N1-N2 sequences in the pattern which realize specific discourse functions in these two genres. Strings belonging to this pattern were retrieved from the two corpora through the corpus interface, Sketch Engine. Findings indicate the prevalence of this frame in the two genres and genre influence on the choice of semantic noun categories. It was also found that the N1-N2 sequences in the pattern are used to realise distinct discourse functions in the two genres. This is one of the first corpus-based studies on university student writing in the Middle East and considering that English is the language of instruction and assessment in many of these countries, these findings have significant pedagogical implications. EFL students in such lingua franca contexts can be supported by a more discipline-specific approach.Â